2019
DOI: 10.33257/phchgd.19.4.754
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Instabilities of Optical Discharges

Abstract: By now technologies, employing optical discharges find ever expanding applications in metering and diagnostic equipment in science, engineering and medicine. Based on the original experimental results authors look into some manifestations of spatial and temporal instabilities of the continuous and periodic pulse optical discharges (COD, POD). Set of the phenomena considered makes a great impact on a performance of laser produced plasmas essential for many applications, such as high brightness broadband light s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…In [11], the study of relatively small (about 1%) pulsations of COD plasma brightness was carried out. Similar pulsations have been observed in broadband emission sources based on COD [9]. It was found that the observed oscillations are of a physical nature.…”
Section: Brightness Fluctuations Of Cod Plasma and Related Convective...supporting
confidence: 81%
See 4 more Smart Citations
“…In [11], the study of relatively small (about 1%) pulsations of COD plasma brightness was carried out. Similar pulsations have been observed in broadband emission sources based on COD [9]. It was found that the observed oscillations are of a physical nature.…”
Section: Brightness Fluctuations Of Cod Plasma and Related Convective...supporting
confidence: 81%
“…The method of obtaining shadow patterns was similar to that used in [11]. A laser-plasma radiation source LPS-50 [9] was used as a point-like light source for the shadowgraphy device. A collimated beam from the point-like source passed through the bulb with plasma and was then focused by an objective that produced a shadowgraphy image in the matrix of the CCD registration camera.…”
Section: Brightness Fluctuations Of Cod Plasma and Related Convective...mentioning
confidence: 99%
See 3 more Smart Citations